Identification and molecular characterization of alcohol dehydrogenase (ADH) and its promoter region in sago palm (Metroxylon sagu) - Yasotha, A/P Sundaraj (Universiti Malaysia Sarawak (UNIMAS), 2008)
Sago palm (Metroxylon sagu) is one of the main economic crops for the state of Sarawak. It is one of the few plant species that thrive on peat swamp area. The waterlogged condition in such areas causes oxygen deprivation to the root part and triggers the anaerobic pathway. Molecular analysis on sago helps in understanding the ability of the palm to tolerate anaerobic conditions. In this study, proteins from various parts of the sago palm such as the roots (dry and submerged) and leaves were extracted successfully. The proteins were subjected for analysis on agarose and polyacralymide gel, and the presence of alcohol dehydrogenase (ADH), lactate dehydrogenase (LDH) as well as superoxide dismutase (SOD) enzymes was detected through specific staining. The results indicated that ADH is present in all analyzed sago tissues and three variants were detected based on migration on gel. However, the banding patterns and the intensity varied among the tissues with the highest expression of ADH and SOD enzymes being reported in the sago shoots. Apart from that, three putative Adh genes from sago palm denoted as M I, M2 and M3 were isolated through Polymerase Chain Reaction (PCR) method using specific primers in this study. Based on the multiple alignment analysis, the three loci are found to be highly diverged and contain a common 23 bp nucleotide which is conserved in other Adh plant species. Phylogeny analysis indicated that the Adh loci of palm (Arecaceae) are segregated from that of other plant Adh families such as from the grass family (poaceae) and Rosaceae, corresponding to the findings of prevIous phylogenetic analysis. All these results concluded that three unique putative Adh genes from sago palm have been successfully isolated. One sago palm Adh gene, referred to here as M2 was used as template for primer designing for DNA walking to further isolate the upstream region which regulates the transcription of the particular gene. The DNA Walking technique has been adapted since genomic library construction yielded a low number of titer, 1.0 x 105 pfulml. Through DNA Walking, a promoter region was successfully identified. Manual and computational analysis of the promoter region revealed the presence of important elements such as TAT A box, CCAA T box and other putative regulatory elements at their respective locations.